LED image display system with mobile APP control. (May 2016) - Chen, Ming-Chih; Ciou, Jian-Yu; Jhang, Guei-Sen; Liang, Yu-Shan
Highlights: Three LED lighting strips perform the LED imaging function on the wheel. The LED lighting strip is controlled by the mobile APP via a Wi-Fi wireless network. It can work normally with wheel speed up to 35 km/hr. Abstract: This work develops LED (Light Emitting Diode) image display system that can display patterns on the spokes of a bicycle. The proposed system of LED lights that are mounted on the wheel can provide safety by producing a beautiful pattern. The main control board and LED lighting strips that determine the displayed pattern are developed using embedded system and electrical circuit designs. A mobile application program is developed to control the lighting hardware remotely; the system communicates with the main control board via a Wi-Fi wireless network interface. The cyclist can change the patterns using the mobile application program or by pushing buttons on the main control board before riding. Six patterns are designed for display using this system, and the pattern can be made to change repeatedly at present intervals. Experimental results reveal that the proposed system performs effectively on the wheel up to a maximum speed of 40 km/hr. Graphical abstract: